The Decreased Growth Hormone Response to Growth Hormone Releasing Hormone in Obesity Is Associated to Cardiometabolic Risk Factors. (21st January 2010) - Cordido, Fernando; Garcia-Buela, Jesús; Sangiao-Alvarellos, Susana; Martinez, Teresa; Vidal, Ovidio
Abstract : The aim of the present study was to evaluate the relationship between GHRH-induced GH secretion in obese premenopausal women and cardiovascular risk markers or insulin resistance. Premenopausal obese women, aged 35–52 years, were studied. GH secretion, IGF-I, serum cardiovascular risk markers, insulin, leptin, mid-waist and hip circumference, total body fat, and truncal fat were measured. Subjects were classified as meeting the criteria for GH deficiency (GHD) when peak GH after stimulation with GHRH was ≤ 3 μ g/L. Mean total and LDL cholesterol, fasting insulin, and HOMA-IR were all higher, in subjects who would have been classified as GH-deficient compared with GH-sufficient. Peak GH secretion after stimulation was inversely associated with fasting insulin (R = − 0.650, P = .012 ), HOMA-IR (R = − 0.846, P = .001 ), total cholesterol (R = − 0.532, P = .034 ), and LDL cholesterol (R = − 0.692, P = .006 ) and positively associated with HDL cholesterol (R = 0.561, P = .037 ). These data strongly suggest a role for insulin resistance in the decreased GH secretion of obesity and that the blunted GH secretion of central obesity could be the pituitary expression of the metabolic syndrome.